Lectures on knot homology and quantum curves - Gukov, Sergei; Saberi, Ingmar (Toplogy and field theories, 2014)
Besides offering a friendly introduction to knot homologies and quantum curves, the goal of these lectures ist to review some of the concrete predictions that follow from the physical interpretation of knot homologies.